Aquatic plant Azolla as the universal feedstock for biofuel production. Issue 1 (December 2016) - Miranda, Ana; Biswas, Bijoy; Ramkumar, Narasimhan; Singh, Rawel; Kumar, Jitendra; James, Anton; Roddick, Felicity; Lal, Banwari; Subudhi, Sanjukta; Bhaskar, Thallada; Mouradov, Aidyn
Abstract Background The quest for sustainable production of renewable and cheap biofuels has triggered an intensive search for domestication of the next generation of bioenergy crops. Aquatic plants which can rapidly colonize wetlands are attracting attention because of their ability to grow in wastewaters and produce large amounts of biomass. Representatives of Azolla species are some of the fastest growing plants, producing substantial biomass when growing in contaminated water and natural ecosystems. Together with their evolutional symbiont, the cyanobacteriumAnabaena azollae, Azolla biomass has a unique chemical composition accumulating in each leaf including three major types of bioenergy molecules: cellulose/hemicellulose, starch and lipids, resembling combinations of terrestrial bioenergy crops and microalgae. Results The growth ofAzolla filiculoides in synthetic wastewater led up to 25, 69, 24 and 40 % reduction of NH4 –N, NO3 –N, PO4 –P and selenium, respectively, after 5 days of treatment. This led to a 2.6-fold reduction in toxicity of the treated wastewater to shrimps, common inhabitants of wetlands. Two Azolla species, Azolla filiculoides andAzolla pinnata, were used as feedstock for the production of a range of functional hydrocarbons through hydrothermal liquefaction, bio-hydrogen and bio-ethanol. Given the high annual productivity of Azolla, hydrothermal liquefaction can lead to the theoretical production of 20.2 t/ha-year of bio-oil and 48 t/ha-year of bio-char. The ethanol production fromAzolla filiculoides, 11.7 × 103  L/ha-year, is close to that from corn stover (13.3 × 103  L/ha-year), but higher than from miscanthus (2.3 × 103  L/ha-year) and woody plants, such as willow (0.3 × 103  L/ha-year) and poplar (1.3 × 103  L/ha-year). With a high C/N ratio, fermentation of Azolla biomass generates 2.2 mol/mol glucose/xylose of hydrogen, making this species a competitive feedstock for hydrogen production compared with other bioenergy crops. Conclusions The high productivity, the ability to grow on wastewaters and unique chemical composition make Azolla species the most attractive, sustainable and universal feedstock for low cost, low energy demanding, near zero maintenance system for the production of a wide spectrum of renewable biofuels.